2020
DOI: 10.1007/s10557-020-06995-x
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Sacubitril/Valsartan against Pathological Cardiac Remodeling by Inhibiting the NLRP3 Inflammasome after Relief of Pressure Overload in Mice

Abstract: Background/aims The persistent existence of pathological cardiac remodeling, resulting from aortic stenosis, is related to poor clinical prognosis after successful transcatheter aortic valve replacement (TAVR). Sacubitril/valsartan (Sac/Val), comprising an angiotensin receptor blocker and a neprilysin inhibitor, has been demonstrated to have a beneficial effect against pathological cardiac remodeling, including cardiac fibrosis and inflammation in heart failure. The aim of this study was to determine whether S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…However, a limitation of this study is that limits on sacubitril solubility within osmotic minipumps did not allow for examination of higher doses of sacubitril that have been more recently tested following oral administration in other experimental cardiovascular models. (Croteau et al, 2020;Li et al, 2020;Tam et al, 2020) It is also possible that differences in NEP expression levels between mouse strains may have influenced results of the present study. (Korshunov et al, 2019) Moreover, other limitations include the choice of animal model (highly related to AngII as the initiating stimulus), difficulties in extrapolating findings from mice to humans, and relevance of the systemic drug concentrations to those achieved in humans.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, a limitation of this study is that limits on sacubitril solubility within osmotic minipumps did not allow for examination of higher doses of sacubitril that have been more recently tested following oral administration in other experimental cardiovascular models. (Croteau et al, 2020;Li et al, 2020;Tam et al, 2020) It is also possible that differences in NEP expression levels between mouse strains may have influenced results of the present study. (Korshunov et al, 2019) Moreover, other limitations include the choice of animal model (highly related to AngII as the initiating stimulus), difficulties in extrapolating findings from mice to humans, and relevance of the systemic drug concentrations to those achieved in humans.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, we observed effects of sacubitril (6 or 9 mg/kg per day) to decrease systolic blood pressure and reduce serum cholesterol and triglyceride concentrations (when combined with 0.5 mg/kg per day valsartan), supporting drug effects at the studied doses and route of administration. However, a limitation of this study is that limits on sacubitril solubility within osmotic minipumps did not allow for examination of higher doses of sacubitril that have been more recently tested after oral administration in other experimental cardiovascular models ( Croteau et al, 2020 ; Li et al, 2020 ; Tam et al, 2020 ). It is also possible that differences in NEP expression levels between mouse strains may have influenced results of the present study ( Korshunov et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, the role of SAC/VAL in suppressing ventricular brosis is well-de ned, but the mechanism behind it remains enigmatical by the current evidence, not to mention the mechanism underlying the inhibition of atrial brosis by SAC/VAL [20][21][22]. Only one study focusing atrial electrical remodeling demonstrated that SAC/VAL could reduce AF susceptibility by inhibiting the calcineurin/nuclear factor of activated T cell (NFAT) pathway [30].…”
Section: Discussionmentioning
confidence: 99%
“…Vaskova et al showed that downregulation of miR-181a exosomes could also be one of the mechanisms by which SAC/VAL improves cardiac function and reduces myocardial brosis in rats with chronic MI [20]. Protein kinase G (PKG) signaling and nuclear factor kappa-light-chainenhancer of activated B cells (NF-κB)/nucleotide-binding oligomerization domain (NOD)-like receptor protein 3 (NLRP3) signaling pathways are also involved in the attenuation of ventricular brosis by SAC/VAL [21,22]. However, all of these published data on the signaling pathways through which SAC/VAL exerts its anti brotic effects are heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…LCZ696, also known as the sacubitril/valsartan, consists of the neprilysin inhibitor sacubitril and the angiotensin receptor blocker valsartan, is a combination drug for use in patients with HF and a reduced ejection fraction ( Lillyblad, 2015 ; Hubers and Brown, 2016 ; Yancy et al, 2016 ). Recently, many studies have explored the anti-inflammatory effect of LCZ696 in basic research, with evidence that this drug can attenuate cardiac dysfunction after myocardial infarction ( von Lueder et al, 2015 ), inhibit oxidative stress, inflammation, and fibrosis, improve renal function in CKD ( Jing et al, 2017 ) and ameliorate NLRP3 after relieving the pressure overload in mice ( Li X. et al, 2020 ). In addition, Xia et al (2017) found that LCZ696 protects cardiac function from doxorubicin-induced DCM by alleviating Drp1-mediated mitochondrial dysfunction.…”
Section: Introductionmentioning
confidence: 99%